2015
DOI: 10.1007/s00429-015-1093-9
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal choice behavior is constrained by brain structure in healthy participants and pathological gamblers

Abstract: The steepness of the delay discounting function shows considerable interindividual differences. Moreover, faster devaluation of future rewards has been consistently observed in pathological gamblers (PGs). Here, we asked whether variability in delay discounting is at least partially driven by differences in the anatomy of gray and white matter. For 40 healthy young subjects (study 1) as well as 15 PG and 15 age-matched healthy controls (HCs, study 2), the individual discounting parameter k was obtained. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…Studies using with smaller sample sizes have reported relationships between DRD and GMV in different regions, such as prefrontal cortex, insular cortex, and striatum (Bjork et al, 2009; Mohammadi et al, 2015; Tschernegg et al, 2015; Wang et al, 2016). Here, the bilateral orbitofrontal cortex and left insula were associated with mAUC after FDR correction and others of these regions were represented among significant associations in the parcellation analysis (e.g., superior frontal gyrus, frontal pole), but did not survive multiple comparison correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using with smaller sample sizes have reported relationships between DRD and GMV in different regions, such as prefrontal cortex, insular cortex, and striatum (Bjork et al, 2009; Mohammadi et al, 2015; Tschernegg et al, 2015; Wang et al, 2016). Here, the bilateral orbitofrontal cortex and left insula were associated with mAUC after FDR correction and others of these regions were represented among significant associations in the parcellation analysis (e.g., superior frontal gyrus, frontal pole), but did not survive multiple comparison correction.…”
Section: Discussionmentioning
confidence: 99%
“…This latter association was reported also in a subsequent study investigating only subcortical regions of the brain (Tschernegg et al, 2015). However, two other studies both found associations with the lateral prefrontal cortex, but not the medial prefrontal cortex (Bjork et al, 2009; Mohammadi et al, 2015). The largest study to date found DRD to be associated with GMV in the frontal pole, dorsolateral prefrontal cortex, medial orbitofrontal cortex, parahippocampal gyrus, striatum, temporal pole, precuneus, and precentral gyrus (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…whether it implements an inhibitory “stop signal” itself or whether it is part of a larger network that provides a more general monitoring function (Hampshire and Sharp, 2015) – its activity has nonetheless previously been linked to addictive disorders. Loss of gray matter in closely adjacent regions has been found in PPG patients relative to control subjects (Mohammadi et al, 2015), and patients with a history of methamphetamine addiction similarly show selective atrophy within this brain area (Tabibnia et al, 2011). Moreover, in a large study of adolescents, activity within the RIFC during a stop signal task strongly differentiated those subjects who had used alcohol, nicotine, and at least one illicit substance from those who had not (Whelan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior insular cortex (AI) has been reported to be causally related to impulsive-compulsive decision making in rats (Belin-Rauscent et al, 2016). This is supported by results from human studies and the involvement of insula areas in decision making (Mohammadi et al, 2016). Specifically, damage to the AI, an important part of the cortical salience network (Menon & Uddin, 2010), may result in a pattern of behavior lacking discrimination between rewards of smaller and larger importance and consequently, not taking action aimed at obtaining a more valuable reward.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, parts of the ventromedial prefrontal cortex, posterior cingulate cortex, and bilateral parietal cortex may be activated proportionally to the subjective value of the delayed reward (Massar, Libendinsky, Weiyan, Huettel, & Chee, 2015). In other studies, the negative correlation between the rate of discounting and gray matter volume in the insula area in the left hemisphere and the orbitofrontal cortex in the right hemisphere, and positive correlation between the gray matter of the frontal pole in the left hemisphere was observed (Mohammadi et al, 2016). This leads to the conclusion that the greater the volume in the insula area of the left hemisphere and the orbitofrontal cortex of the right hemisphere, the more steeply discounted the rewards.…”
Section: Introductionmentioning
confidence: 74%